The Cyclic Hydrogen‐Bonded 6‐Azaindole Trimer and its Prominent Excited‐State Triple‐Proton‐Transfer Reaction. Issue 18 (23rd March 2018) - Tu, Ting‐Hsun; Chen, Yi‐Ting; Chen, Yi‐An; Wei, Yu‐Chen; Chen, You‐Hua; Chen, Chi‐Lin; Shen, Jiun‐Yi; Chen, Yi‐Han; Ho, Ssu‐Yu; Cheng, Kum‐Yi; Lee, Shern‐Long; Chen, Chun‐hsien; et al.
Abstract: The compound 6‐azaindole undergoes self‐assembly by formation of N(1)−H⋅⋅⋅N(6) hydrogen bonds (H bonds), forming a cyclic, triply H‐bonded trimer. The formation phenomenon is visualized by scanning tunneling microscopy. Remarkably, the H‐bonded trimer undergoes excited‐state triple proton transfer (ESTPT), resulting in a proton‐transfer tautomer emission maximized at 435 nm (325 nm of the normal emission) in cyclohexane. Computational approaches affirm the thermodynamically favorable H‐bonded trimer formation and the associated ESTPT reaction. Thus, nearly half a century after Michael Kasha discovered the double H‐bonded dimer of 7‐azaindole and its associated excited‐state double‐proton‐transfer reaction, the triply H‐bonded trimer formation of 6‐azaindole and its ESTPT reaction are demonstrated. Abstract : Trinity Roots : 6‐azaindole undergoes self‐assembly by formation of N(1)−H⋅⋅⋅N(6) hydrogen bonds (H bonds), to form a cyclic, triply H‐bonded trimer. The H‐bonded trimer undergoes excited‐state triple proton transfer (ESTPT), resulting in a proton‐transfer tautomer emission maximized at 435 nm.